[PP.08.17] COMPARISON OF FOUR QUESTIONNAIRES IN EVALUATING THE PREVALENCE OF HIGH INDEX OF CLINICAL SUSPICION OF OSA IN TREATED HYPERTENSIVE PATIENTS - DATA FROM THE POL-FOKUS STUDY. (September 2017) - Talarowska, P.; Wolf, J.; Prejbisz, A.; Klocek, M.; Gasowki, J.; Topor-Madry, R.; Lesniak, W.; Czarnecka, D.; Kawecka-Jaszcz, K.; Narkiewicz, K.; Januszewicz, A.
Abstract : Objective: Polysomnography remains a gold standard for the diagnosis of obstructive sleep apnoea (OSA). Due to limited availability and high number of hypertensive patients with OSA several questionnaires were introduced to select patients at high risk of OSA. The purpose of this evaluation was to compare the prevalence and clinical characteristics of patients at high risk of OSA selected on the basis of four different questionnaires in a large sample of patients with hypertension (HTN). Design and method: In a sub-study of the cross-sectional questionnaire-based observational Pol-Fokus study we included 3477 hypertensive patients (mean age 62.7 +/- 12.7 years; F 57.5%, M 42.5%) attending a routine visit in primary or specialist care. To be included patients had to be > 18 years old and had to be treated for at least 12 months with antihypertensive drugs. We defined HTN control as office blood pressure (BP) levels both <140 mmHg/<90 mmHg. High risk of OSA was assessed by means of STOP-Bang and Berlin questionnaires (BQ), NoSAS score and Epworth Sleepiness Scale (ESS). Cardiovascular (CV) risk was evaluated according to 2013 ESH/ESC guidelines. Results: The frequency of patients at high risk of OSA depended on the questionnaire used: NoSAS (63, 7%), BQ (41.0%), STOP-Bang (33.9%) and ESS (15.1%). Highest concordance of results was found between STOP-Bang and ESS (68.7%) and between STOP-Bang and BQ (75.5%). When STOP-Bang was used as a reference test the sensitivity and selectivity of other tests were for ESS (26% and 90%), BQ (76% and 77%) and NoSAS (91% and 50%). Irrespectively of the questionnaire used, patients at high risk of OSA were characterized by higher percentage of males, lower rate of HTN control, higher prevalence of CV disease or chronic kidney disease and by higher rate of high/very high cardiovascular risk. Conclusions: Our results showed discordance in results of commonly used questionnaires for selection of patients at high risk of OSA. However there were no major differences in clinical characteristics of patients at high risk of OSA selected by means of those questionnaires.